Myocarditis and diffuse skeletal muscle oedema: new features of neuromyelitis optica spectrum disorder? A case report. (January 2014) - Cosgrove, Jeremy; Alli, Saira; Ramadan, Hawraman; Ford, Helen L
We present a case report of newly diagnosed neuromyelitis optica spectrum disorder (NMOSD) with associated myocarditis and diffuse oedema of the pelvic and anterior compartment thigh muscles on magnetic resonance imaging. Aquaporin 4 antibodies are expressed in skeletal myofibres but involvement of skeletal muscle is rarely reported in NMOSD and myocarditis has not previously been described in this context. This case highlights the need for further research into the involvement of cardiac and skeletal muscle in NMOSD.